EFFICACY OF SALBUTAMOL DELIVERED THROUGH A METERED DOSE INHALER & SPACER IN CHILDREN WITH ACUTE EXACERBATION OF ASTHMA - Ali Mujtaba Tahir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess efficacy of salbutamol delivered through metered dose inhaler (MDI) - spacer in paediatric patients with acute exacerbation of asthma.